2017
DOI: 10.1097/acm.0000000000001590
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging Telemedicine Infrastructure to Monitor Quality of Operating Room to Intensive Care Unit Handoffs

Abstract: Purpose To analyze in-room video recordings of operating room (OR) to intensive care unit (ICU) handoffs to determine tempo and quality of team interactions on nights and weekends compared with weekdays, and to demonstrate how existing telemedicine technology can be used to evaluate handoffs. Method This prospective observational study of OR-to-ICU bedside handoffs was conducted in the surgical ICU of the Hospital of the University of Pennsylvania in July 2014–January 2015. Handoff video recordings were obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“… 48 One study used video analysis of handoffs and found that surgeon handoffs are actually better on nights and weekends than on weekdays. 49 Unobtrusive methods like video analysis may inform targeted changes to care protocols that alleviate observed weekend effects.…”
Section: Discussionmentioning
confidence: 99%
“… 48 One study used video analysis of handoffs and found that surgeon handoffs are actually better on nights and weekends than on weekdays. 49 Unobtrusive methods like video analysis may inform targeted changes to care protocols that alleviate observed weekend effects.…”
Section: Discussionmentioning
confidence: 99%
“…It may be explained with the findings of Barry and Capozzi. They believe that using existing organizational infrastructure improves education, compliance with institutional handoff policies, and tele-monitoring services ( 36 , 37 ). Also, according to Saghaeiannejad-Isfahani et al, the implementation of telemedicine involves improving the technical infrastructure ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…47 In summary, trends toward automation and algorithmic clinical and operational decision-support systems are strongly evident in most health care practices, including anesthesiology. 48 In the future, as troves of data are generated from electronic records, notes, images, sensors and devices, it will become imperative for health care systems to employ AI-enabled technologies to help clinicians and researchers develop greater insights from these multidimensional data sets in order to improve monitoring, diagnostics, and therapies in patient care. While technology innovations are likely to have a significant impact on anesthesiology practices, challenges in adoption remain and will require focused attention.…”
Section: Telemedicine In Anesthesiologymentioning
confidence: 99%